A comparative study of vit D3 levels with preterm premature rupture of membranes in pregnant mothers referred to the Bent Alhoda Hospital of Bojnurd city in 2020-2021 - Kataneh Kazemi; Mahboubeh Ghorbani; Maryam Tavakoli; Afsaneh Nozadi; Mohsen Rakhsha (Mashhad University of Medical Sciences, 2022)
Introduction: Due to the importance of premature rupture of membrane and its complications, this study was performed aimed to compare between serum vitamin D3 levels and preterm premature rupture of membranes (PPROM) in two groups of pregnant women with PPROM and mothers with rupture of membrane after 37 weeks. Methods: This cross-sectional (descriptive-analytical) study was performed in 2020-2021 on 60 pregnant mothers admitted for delivery in Bent Al-Hoda Hospital in Bojnourd during 6 months. 5cc of blood sample was taken from the selected population to measure the level of vitamin D and was assessed in the two groups. Data were analyzed by SPSS software (version 16) and Mann-Whitney test and linear regression. P<0.05 was considered statistically significant. Results: In the present study, the mean and standard deviation of serum vitamin D3 level in the group of mothers with PPROM was 18.31±9.15 ng/cc, and in mothers with premature rupture of the membranes after 37 weeks was 20.93±8.68 ng/cc. There was no significant difference between the two groups in terms of serum levels of vitamin D3 (P=0.54). Conclusion: There was no relationship between serum levels of vitamin D3 in the two groups of women with PPROM and women with premature rupture of the membranes after 37 weeks.